Phenotypic and Genotypic Identification of Metallobetalactamase Genes in Resistant Enterobacteriaceae Isolated from Medical Centers in Isfahan - Alizadeh, Houri; Khodavandi, Alireza; Alizadeh , Fahimeh; Bahador, Nima (Novelty in Biomedicine, 2024)
Background: The emergence of resistant Enterobacteriaceae and the abundance of antibiotic-resistant genes is one of the major problems of the global health system. The present study aimed to determine the phenotypic and genotypic expression levels of metallobetalactamase coding genes (blaVIM, blaNDM, blaIMP, blaSIM, blaSPM, and blaGIM) in Enterobacteriaceae isolates (Escherichia, Enterobacter, Citrobacter, Klebsiella, and Serratia) from patients referred to the clinical centers in Isfahan city and typing of these isolates. Materials and Methods: Enterobacteriaceae isolates were identified and isolated after sample collection. Antibiotic sensitivity pattern was investigated by disk diffusion method. MIC was performed in carbapenem-resistant isolates by the E-test method, and the frequency of strains with multidrug resistance was determined. The presence of metallobetalactamase genes was investigated phenotypically using a combined disk test and modified Hodge test. The genotypic identification of the above genes was done by PCR and sequencing techniques. Finally, PCR based on the sequence of repetitive elements was performed for molecular typing of metallobetalactamase-producing Enterobacteriaceae. Results: In the present study, 580 isolates of Enterobacteriaceae were isolated by examining 3500 samples. Klebsiella and Escherichia were the most common isolates, and the frequency of MDR was 60% in Klebsiella and 59.53% in Escherichia. Moreover, MIC results showed that 33.7% Klebsiella, 4.1% Escherichia, 5.7% Enterobacter, 3.5% Citrobacter, and 5.5% Serratia were resistant to carbapenems. Frequency of isolates with multidrug resistance in Escherichia (MDR 59.53% and XDR 1.5%), Klebsiella (MDR 60%, XDR% 3 and PDR 0.8%), Enterobacter (MDR 44%), Citrobacter (MDR 53.5%) and Serratia (MDR 55.5%) were reported. Metallobetalactamase production was confirmed by phenotypic analysis in Escherichia (1.8%) and Klebsiella (10.4%). Genotypic tests showed that blaSIM, blaSPM, and blaGIM genes were absent in any Enterobacteriaceae isolates. The presence of blaVIM, blaIMP, and blaNDM genes was confirmed in 6.2% of Klebsiella isolates and 1.3% of Escherichia isolates. The frequency of detected metallobetalactamase genes in Klebsiella and Escherichia isolates was 4.58% and 1.39% for blaVIM, 0.83% and 1.39% for blaIMP and 0.83% and 1.39% for blaNDM. The rep-PCR results showed that 11 metallobetalactamase-producing Klebsiella isolates are in 4 main groups, and 9 Escherichia isolates and 4 Enterobacter isolates are classified in two main clusters. Conclusion: The present study shows the prevalence of Klebsiella and Escherichia isolates and their resistance to metallobetalactamase-producing Enterobacteriaceae. These genes in the horizontal transfer of antibiotic resistance identification of metallobetalactamase-producing isolates in clinical environments are essential to reduce the spread of antibiotic resistance. The high homology of resistant isolates of Enterobacteriaceae inclinical samples indicates the high power of these genotypes in causing infection in hospitalized patients, which can play an important role in increasing antibiotic resistance.